2016
DOI: 10.1590/s0102-865020160080000005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extract of the Vigna angularis in rats subjected to an experimental model of moderate chronic kidney disease

Abstract: PURPOSE:To evaluate the effect of the aqueous extract of the Vigna angularis, popularly known as "Azuki beans", in rats subjected to an experimental model of moderate chronic kidney disease. METHODS:Thirty rats underwent two surgeries - Ormrod and Miller (1980) -to obtain Moderate Chronic Kidney Disease (CKD-M).The animals were randomized into 3 groups. Group 1 (Control): distilled water. Group 2 (Azuki): Vigna angularis 5% aqueous extract.Group 3 (Treatment): 10mg/kg of enalapril maleate. The rats received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It represented a decrease of 52.4% by group and 71.3% in the cancer/rat ratio. Other studies also showed better activity in lower doses in natural chemotherapy treatment, including modulation in epithelial dysplasia and, specifically, moderate dysplasia (Ribeiro and Salvadori 2007;Helli et al 2016) , (Renugadevi and Prabu 2010;Santos-Nascimento et al 2015;Baracho et al 2016) , (Mehdipour et al 2013) and other researchers observed better results in the highest dose, including epithelial acantosis and epithelial dysplasia (Mehdipour et al 2013) , (Yoshida et al 2005). In addition, reduction of squamous cell carcinoma in situ, microinvasive and invasive have also been described.…”
Section: Discussionmentioning
confidence: 89%
“…It represented a decrease of 52.4% by group and 71.3% in the cancer/rat ratio. Other studies also showed better activity in lower doses in natural chemotherapy treatment, including modulation in epithelial dysplasia and, specifically, moderate dysplasia (Ribeiro and Salvadori 2007;Helli et al 2016) , (Renugadevi and Prabu 2010;Santos-Nascimento et al 2015;Baracho et al 2016) , (Mehdipour et al 2013) and other researchers observed better results in the highest dose, including epithelial acantosis and epithelial dysplasia (Mehdipour et al 2013) , (Yoshida et al 2005). In addition, reduction of squamous cell carcinoma in situ, microinvasive and invasive have also been described.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to traditional therapy, scientists concentrate on the recent use of dietary supplements and novel natural products or their derivatives to reduce the high risk of CKD and limit the severity of this disease. In this regard, numerous studies and reviews have documented the potential impact of compounds with anti-inflammatory and antioxidant activities in CKD treatment [ 12 , 13 , 57 , 58 ]. Other studies have indicated that dietary interventions are essential in lowering inflammation and oxidative stress in CKD patients [ 57 ].…”
Section: Role Of Antioxidants In the Prevention Of Ckdmentioning
confidence: 99%
“…Some plant extracts have been investigated previously in the treatment of CKD due to their possible therapeutic properties [ 58 , 59 , 60 ]. In this regard, recent experimental studies investigated the effects of Phylanthus niruri leaves aqueous extract (PN) on renal functions, structural alteration, and biomarkers of oxidative stress, inflammation, fibrosis, apoptosis, and proliferation in the diabetes mellitus (DM) rat model.…”
Section: Role Of Antioxidants In the Prevention Of Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the adzuki beans cultivated in Eastern Asian countries are red in color. This legume is rich in dietary fibers, proteins, minerals, vitamin A, vitamin B9 and folate [3] . Due to its biochemical components, V. angularis has been evaluated as a new treatment option.…”
Section: Abstract: Vigna Angularis (Adzuki Bean) Total Polyphenolsmentioning
confidence: 99%